The crucial role of the regulatory mechanism of the Atg1/ULK1 complex in fungi - Cai, Ying-Ying; Li, Lin; Zhu, Xue-Ming; Lu, Jian-Ping; Liu, Xiao-Hong; Lin, Fu-Cheng (Frontiers in Microbiology, 2022)
Autophagy, an evolutionarily conserved cellular degradation pathway in eukaryotes, is hierarchically regulated by autophagy-related genes (Atgs). The Atg1/ULK1 complex is the most upstream factor involved in autophagy initiation. Here，we summarize the recent studies on the structure and molecular mechanism of the Atg1/ULK1 complex in autophagy initiation, with a special focus on upstream regulation and downstream effectors of Atg1/ULK1. The roles of pathogenicity and autophagy aspects in Atg1/ULK1 complexes of various pathogenic hosts, including plants, insects, and humans, are also discussed in this work based on recent research findings. We establish a framework to study how the Atg1/ULK1 complex integrates the signals that induce autophagy in accordance with fungus to mammalian autophagy regulation pathways. This framework lays the foundation for studying the deeper molecular mechanisms of the Atg1 complex in pathogenic fungi.